Pomen motivacije za razvoj, pripadnost in delovno uspešnost upravnih enot v Republiki Sloveniji - Marzel, Kornelija (Teorija in praksa, 2000)
The purpose of the article is to underline idea that human resource management can take place in administrative units (as institutions which are part of the executive authority and mean territorial distribution of authority only). As a result, greater sence of commitment influences better work efficiency. Along with theoretical point of view of human resource management, special emphasis is put on processes of motivation, human resource development, commitment and efficiency. The results of the survey carried out in administrative units of the Koroška region are presented in the article as well. In addition, some recommendations to be put into practice are presented.
Keywords: človeški viri; management; kadri; delovna uspešnost; javna uprava; državna uprava; Slovenia; Slovenija